The Expression of Formyl Peptide Receptor 1 is Correlated with Tumor Invasion of Human Colorectal Cancer - Li, Shu-Qin (Sci Rep, 2017)
Formyl peptide receptors (FPRs) are G protein-coupled chemoattractant receptors expressed mainly in phagocytic leukocytes. High expression of FPRs has also been detected in several cancers but the functions of FPR1 in tumor invasion and metastasis is poorly understood. In this study, we investigated the expression of FPRs in primary human colorectal cancer (CRC) and analyzed the association of FPRs expression with clinicopathological parameters. The levels of FPRs mRNA, especially those of FPR1, were significantly higher in colorectal tumors than in distant normal tissues and adjacent non-tumor tissues. FPR1 mRNA expression was also associated with tumor serosal infiltration. FPR1 protein expression was both in the colorectal epitheliums and tumor infiltrating neutrophils/macrophages. Furthermore, the functions of FPR1 in tumor invasion and tissue repair were investigated using the CRC cell lines SW480 and HT29. Higher cell surface expression of FPR1 is associated with significantly increased migration in SW480 cells compared with HT29 cells that have less FPR1 membrane expression. Finally, genetic deletion of fpr1 increased the survival rate of the resulting knockout mice compared with wild type littermates in a mouse model of colitis-associated colorectal cancer. Our data demonstrate that FPR1 may play an important role in tumor cell invasion in CRC patients.